Energy demand modeling for low carbon cities in Thailand: A case study of Nakhon Ratchasima province - Atit Tippichai; Kattreeya Teungchai; Atsushi Fukuda (International Journal of Renewable Energy Development, 2023)
Nakhon Ratchasima is one of the northeastern cities which has been promoted as one of the low-carbon cities in Thailand. The study aims to evaluate policies and measures on greenhouse gas (GHG) emissions mitigation to meet the target at the provincial level. The Low Emissions Analysis Platform (LEAP) is used as a modeling tool to simulate energy demand for each economic sector. The 2019 data is set as a base year, using top-down and bottom-up approaches depending on the availability of data for the analysis. The model consists of two scenarios: (1) Business-as-usual (BAU) scenario and Low carbon scenario (LCS). Transport and industry sectors are the most energy-consuming and CO2-emitting sectors in Nakhon Ratchasima Province. In the LCS case, the final energy demand and CO2 emissions in 2050 will be reduced by about 40% compared to the BAU case. In addition, CO2 emissions in Nakhon Ratchasima Province will peak around 2038, this is not the case with BAU. The study could predict future energy demand and propose a way forward to reducing GHG emissions at the provincial level.